The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep21194
|View full text |Cite
|
Sign up to set email alerts
|

Systematic microRNAome profiling reveals the roles of microRNAs in milk protein metabolism and quality: insights on low-quality forage utilization

Abstract: In this study, we investigated the molecular regulatory mechanisms of milk protein production in dairy cows by studying the miRNAomes of five key metabolic tissues involved in protein synthesis and metabolism from dairy cows fed high-and low-quality diets. In total, 340, 338, 337, 330, and 328 miRNAs were expressed in the rumen, duodenum, jejunum, liver, and mammary gland tissues, respectively. Some miRNAs were highly correlated with feed and nitrogen efficiency, with target genes involved in transportation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 56 publications
4
37
0
2
Order By: Relevance
“…Dairy cows fed AH-based diets had higher milk yield and milk protein content than cows fed corn stover (CS)-based diets6910 and RS-based diets611. In addition, low milk protein production on low-quality forages (CS and RS) was found to be associated with low feed- and nitrogen-use efficiency in mammary glands in a microRNA transcriptomic study7. However, further studies are still required to more completely define the differences in mammary gland responses to alternative dietary energy and protein profiles provided by rations with differing forage sources.…”
mentioning
confidence: 97%
“…Dairy cows fed AH-based diets had higher milk yield and milk protein content than cows fed corn stover (CS)-based diets6910 and RS-based diets611. In addition, low milk protein production on low-quality forages (CS and RS) was found to be associated with low feed- and nitrogen-use efficiency in mammary glands in a microRNA transcriptomic study7. However, further studies are still required to more completely define the differences in mammary gland responses to alternative dietary energy and protein profiles provided by rations with differing forage sources.…”
mentioning
confidence: 97%
“…Significant differentially expressed (after corrected for multiple testing P-value <0.01 and absolute fold change >2) mature miRNAs were observed in all tissues except in black skin (Table 2; Figure 3A). Known miRNAs with high tissue-specificity showed significant differential expression in our analysis, such as miR-375 in adrenal gland (Ludwig et al 2016; Gai et al 2017), miR-219 in brain caudal lobe and brain cerebellum (Ludwig et al 2016), and miR-122 in liver (Jopling 2012; Szabo and Bala 2013; Modepalli et al 2014; Wang et al 2016a). No novel miRNAs were found to be up-regulated in any tissues, but some novel miRNAs were down-regulated in adrenal gland, brain cerebellum, lung, ovary, spleen and thyroid.…”
Section: Resultsmentioning
confidence: 84%
“…Micro RNAs (miRNAs) are a class of single-stranded, short-length (typically 19-24nt), endogenous, non-coding RNAs (ncRNAs) that are involved in almost all biological processes, including development, differentiation, immunity, reproduction and longevity (Kloosterman and Plasterk 2006; Hasuwa et al 2013; Renthal et al 2013; Li and Belmonte 2015; Mehta and Baltimore 2016; Wang et al 2016a; Cowled et al 2017; loannidis and Donadeu 2017; Bartel 2018). Close to three decades of miRNA studies have revealed that miRNAs have broadly conserved biogenesis and conserved target sites at the three prime untranslated regions (3’UTRs) of the messenger RNAs (mRNAs) in eukaryotes (Bartel 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The profiles of miRNAs in bovine MG tissue or milk have been investigated using different approaches, such as microarray [48,49], genome sequencing [4] and RNA sequencing [50][51][52][53][54][55][56][57]. A total of 496 miRNA genes were identified following sequencing of the cattle genome of which 135 were novel [4].The expression profiles of miRNAs in MG tissues and cells facilitate discovery of novel miRNAs and also identification of candidate miRNAs for different cell types, lactation stages, periods, disease response and so on.…”
Section: Cattlementioning
confidence: 99%
“…A change in diet that interferes with energy balance has been shown to change miRNA expression pattern in cow liver [103]. Wang et al [104] fed cows with high-and low-quality forage diets (corn stover and rice straw) and showed that miR-125b, miR-141, miR-181a, miR-221 and miR-15b changed their expression patterns across different tissues including MG. We have examined the expression pattern of miRNAs following MG adaptation to dietary supplementation with 5% linseed oil or 5% safflower oil using miRNA sequencing and identified seven differentially regulated miRNAs, including six upregulated (miR-199c, miR-199a-3p, miR-98, miR-378, miR-148b and miR-21-5p) and one downregulated (miR-200a) by both linseed and safflower oil. The target genes of these seven miRNAs have functions related to gene expression and general cellular metabolism and are enriched in four pathways of lipid metabolism (3-phosphoinositide biosynthesis, 3-phosphoinositide degradation, D-myo-inisitol-5-phosphate metabolism and the superpathway of inositol phosphate compounds) [51].…”
Section: Nutritional Modulation Of Microrna Expression and Functionmentioning
confidence: 99%